Skew Semi-Heyting Algebras - Berhanu Assaye Alaba; Mihret Alamneh; Yeshiwas Mebrat Gubena (LPPM Institut Teknologi Sepuluh Nopember, 2018)
In this paper, we introduce the concept of skew semi-Heyting algebra and extend the notions of semi-Heyting algebras. We characterize a skew semi-Heyting algebra as a skew Heyting algebra interms of a unique binary operation on which an induced binary operation is defined, and some algebraic properties on it.